2021
DOI: 10.1002/ejlt.202100092
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Liquid Phase Behaviors of Binary Mixtures of Various Partial Acylglycerols by Differential Scanning Calorimetry

Abstract: Monoacylglycerol (MAG), diacylglycerol (DAG), and triacylglycerol (TAG) are impurities in biodiesel and a major cause of precipitation. Understanding the behavior of such acylglycerols is essential for predicting biodiesel cold flow properties (CFPs). The previous study on MAG/MAG binary mixtures shows that they tend to solidify by forming molecular compounds. In contrast, TAG/TAG mixtures, which have been studied extensively, are commonly eutectic or monotectic systems, in which each component solidifies sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In addition, MAGs are generally present in higher concentration and have slightly higher melting points than DAGs and TAGs, meaning that MAGs will generally determine the liquidus temperature of biodiesel. Therefore, it is suggested that only the compound formation of MAG/MAG should be considered to predict the liquidus temperature of biodiesel [27]. This suggestion was supported even for multicomponent systems by the results of Figure 4, which shows no significant difference in liquidus temperature with the presence of DAG in the mixture.…”
Section: Biodiesel Surrogatesmentioning
confidence: 82%
See 2 more Smart Citations
“…In addition, MAGs are generally present in higher concentration and have slightly higher melting points than DAGs and TAGs, meaning that MAGs will generally determine the liquidus temperature of biodiesel. Therefore, it is suggested that only the compound formation of MAG/MAG should be considered to predict the liquidus temperature of biodiesel [27]. This suggestion was supported even for multicomponent systems by the results of Figure 4, which shows no significant difference in liquidus temperature with the presence of DAG in the mixture.…”
Section: Biodiesel Surrogatesmentioning
confidence: 82%
“…In the CF model, not only MAG/MAG but also, for example, MAG/DAG or DAG/DAG may form compounds. However, our previous studies of acylglycerol binary systems showed that all combinations of acylglycerols except MAG/MAG mixtures tended to follow the NSS model [27], meaning that DAGs and TAGs do not interact with MAGs and solidify independently as pure components. In addition, MAGs are generally present in higher concentration and have slightly higher melting points than DAGs and TAGs, meaning that MAGs will generally determine the liquidus temperature of biodiesel.…”
Section: Biodiesel Surrogatesmentioning
confidence: 88%
See 1 more Smart Citation
“…In the melting process of binary blends containing 50%–90% PKS, a crystallization peak appeared, signifying solid–liquid–solid or melt‐mediated transformations in the binary blends. Initially, a polymorphic crystal form melted, recrystallized into a more stable form around 15°C, and then melted once again (Joshi et al., 2020; Seniorita et al., 2022). This phenomenon was consistent with the presence of eutectic systems when components in binary blends possessed significantly different molecular volumes, shapes, and polymorphic forms, yet similar melting points, as indicated by the iso‐solid diagram.…”
Section: Resultsmentioning
confidence: 99%